Fly me to the moon: from corporate branding orientation to retailer preference and business performance. Issue 1 (3rd November 2021) - Foroudi, Pantea; Foroudi, Mohammad Mahdi; Palazzo, Maria; Nguyen, Bang
Abstract : Purpose: The airline aviation industry is both capital-intensive and competitive. Hence, the evolution of the sector needs original marketing strategies. To study the relationships between corporate branding and corporate image, taking into account two views, namely, corporate strategy and corporate expression in airline identity, this paper aims to analyze the main indicators of the corporate branding that affect the outcomes of the corporate image. Design/methodology/approach: To inspect the theories, the foundational configural model was assessed through the perceptions of 395 employees in Indian aviation companies. By using complexity theory, this study matched the concept of equifinality and it examined the data via a fuzzy set qualitative comparative analysis. Findings: Findings show that corporate strategy positively influences the corporate image and corporate expression. Corporate expression offers the verbal and visual facets of a brand. Surprisingly, the paper shows that there is no link between corporate expression and corporate image. It also suggests that corporate expression, including corporate community, corporate promise and corporate personality, are all components of a corporate brand and do not influence the corporate image. Finally, the study highlights that corporate image positively affects superior business performance, which influences superior retailer preference. Research limitations/implications: The study identifies the corporate identity's indicators (corporate strategy and corporate expression) that affect the corporate image, which results in stronger, superior business performance and retailer preference. It suggests that managers in the airline industry should follow the recommendations of this research by adopting more objective and fairer procedures to attain superior business performance and retailer preference. In addition, the continued growth and the financial impact of the airline sector require the use of pioneering branding strategies. Future study is needed in various nations to advance the generalizability of the research findings. Originality/value: To the best of the authors' knowledge, the paper is the first to study corporate brand, its sub-dimensions (corporate strategy and corporate expression) and their individual links to brand image, which involves experience, relationships and visual identity.